PENGELOLAAN PENDIDIKAN BERBASIS KEBIJAKAN GENDER DI SALAH SATU SEKOLAH DASAR BANTEN - ana nurhasanah; arita Marini; Mohamad Syarif Sumantri (FIP Unimed, 2021)
One of the important things that need to be considered in the management ofelementary school education (SD) is to build education that is equal. From the beginning,efforts must be made to implement gender justice in primary school education. This studyaims to determine the implementation of primary school education management based ongender policies and indicators of gender policy-based education management inelementary schools at SD Negeri Serdang 1, Kramatwatu District, Serang Regency. Theresearch method used is narrative research (Cresswell, 2012), with interview techniquesand documentation analysis. The results showed that the implementation of gender-basededucation management in primary schools has been carried out by referring to genderresponsive school indicators.Keywords: Education Management, Gender Policy, Elementary School